The Metabolism of L-Arginine and Its Importance in Immune Function - Su, Ben; Rudak, Patrick; Yin, Charles (The Meducator, 2014)
The importance of arginine in maintaining the homeostasis of the immune system is a focus of the emerging field of immunometabolism, and is representative of the growing body of knowledge on the role of metabolites in immune function. Arginine plays a critical role in the function of the immune system, as arginine deficiency in macrophages leads to a defect in nitric oxide production. Consequently, this results in decreased macrophage elimination of pathogens. Additionally, myeloid suppressor cells (MSCs) have been shown to exert regulatory effects on activated T-cells by utilizing arginine metabolism in various different pathways. Decreased levels of arginine have also been observed to interfere with proper B-cell maturation and IgM production, all of which ultimately impair the adaptive immune response. In this review, the importance of arginine in the context of immune system is explored.